Análisis de las estrategias comunicacionales de la Unidad Educativa Kolping y su impacto en la parroquia Yaruquíes, julio a diciembre 2019 - Buenaño Moreno, Marco Vinicio (2021)
Designed to determine the communication strategies for the institution and the impact it causes in the Yaruquíes- Chimborazo parish, the research work begins with the approach of the problem itself that framed in knowing and exposing the current state of the educational establishment and its viability, continuing with the general objective and specifics that contribute to the development and are the guide for the whole project, followed by the theoretical framework that covers and presents scientific compilations of the various topics: functionalist theory, institutional communication, communication strategies, social networks, and the Kolping Educational Unit, in order to obtain precision in the contents. The research methodology was descriptive and field method, concerning the population and sample; in this case, the population surveyed was 243 people. To deploy this exploration, data collection techniques and instruments were applied, in addition to procedural techniques for the analysis of results. Likewise, 64% of the data obtained indicated that this establishment presents little information to know their work, supporting the research. The conclusions aim to understand the lack of strategies and digital tools that allow for the massification of information and services promulgation. Together, the recommendations are directed at the institution to work with the eight communication strategies to improve the image and information management's strengthening. Keywords: Communication strategies, Kolping, impact, analysis, Yaruquies, digital Reviewed by: Msc Elizabeth Diaz 0603277765 English professor